Mathematical representation and analysis of articular surfaces: application to the functional anatomy and palaeo-anthropology of the ankle joint - Webb, Christie Peter (University of the Witwatersrand, Johannesburg, 1990)
This thesis is a study of quantifiable variation in the geometric shape of the superior articular surface of the talus of higher primates, with special reference to fossil tali of Plio-Pleistocene hominids. (Abbreviation abstract).
A thesis submitted in fulfillment of the requirements for the degree of Doctor of Philosophy, to the Faculty of Health Science, School of Anatomical Science, University of the Witwatersrand, Johannesburg, 1990.
Keywords: Physical anthropology; Human evolution; Fossil hominids; Human locomotion; Anklebone; UCTD; Mathematical models; Evolution; Anatomy